A partial feedback linearization based control design and simulation for three phase shunt active power filter. (September 2016) - Mohapatra, Soumya Ranjan; Ray, Pravat Kumar; Beng, Gooi Hoay
Highlights: Partial feedback linearization technique used to control design of an active power filter (APF). Averaged dynamic model of APF has been derived from single phase equivalent circuit of the system. Control input to the linearized system obtained considering stability of the complete APF system. Stability of the internal dynamics of system is analyzed considering zero dynamics of the system. Abstract: This paper exploited partial feedback linearization technique to control design of a three phase shunt active power filter (APF) by considering it as a Multiple Input Multiple Output (MIMO) system. The averaged dynamic model of the three phase APF has been derived considering the single phase equivalent circuit of the system. This averaged dynamic model is used to partially feedback linearize the MIMO nonlinear system dynamics. New control input to the linearized system is obtained considering the stability of the complete APF system. After that, control input to APF is derived by nonlinear transformation. Stability of the internal dynamics of the system is analyzed considering zero dynamics of the system. MATLAB/Simulink based simulation results are provided to validate the performance of the controller.